PENGGUNAAN METODE AUDIO VISUAL DAN MEDIA PEMBELAJARAN MICROSOFT POWER POINT TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 86 KOTA BENGKULU - Septi Yuliza (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
This research  is to know whether  there is influence from using audiovisual method and microsoft power point learn- ing media  to motivation of student  learning on Islamic Education subject in SD Negeri 86 Kota Bengkulu.This research  uses quantitative approach. The population is all elementary school students  86 Bengkulu City. sampling is done by purposive sampling  that is determination technique with certain  consideration. Data  were analyzed  using simple linear re- gression test. The results showed  that the variable  of audiovisual method (X1) and  microsoft power  point (X2) had  a positive effect on students’  learning  motivation State  primary  school 86 Bengkulu  city. In the test, it can be seen  that the influence  of visual audio  method variable  (X1) on student  learning  motivation (Y) is 9,3%,  while the rest 90,7%  influenced  by other  than variable  X1. Variable  of learning  media  of Microsoft Power  Point  (X2) can  influence  Student Motivation  Motivation  variable equal to 34,5%,  while the rest of 65,5%  influenced  by other variable besides variable of learning media  Microsoft power point. Together, the variables  of audio  visual method and  learning  media  of Microsoft power  point can influence  student’s  learning motivation equal  to 34,6%,  while the rest of 65,4%  influenced  by other  variable  beside  variable  of audio  visual method and Microsoft Power Point learning media